Comparison of swimming velocity between age-group swimmers through discrete variables and continuous variables by Statistical Parametric Mapping - Morais, Jorge E.; Barbosa, Tiago M.; Lopes, Tiago; Moriyama, Shin-Ichiro; Marinho, Daniel A. (Sports Biomechanics, 2024)
The aim of this study was to compare the swimming velocity in front-crawl between age-group swimmers using discrete variables against Statistical Parametric Mapping (SPM). The sample consisted of 30 young male swimmers divided into three groups (each with 10 swimmers) based on their age (group #1: 13.60 ± 0.84 years; group #2: 15.40 ± 0.32 years; group 3: 16.39 ± 0.69 years). Swimmers performed three maximal trials in front-crawl. The best performance was used for analysis. Comparison of swimming velocity between groups was analysed using discrete variables and as a continuous variable (SPM). As a discrete variable, the mean swimming velocity showed a significant difference between groups (p < 0.05). Moreover, when analysed by SPM, swimming velocity showed a significant difference (p = 0.021) between the ~ 44% and ~ 51% of the stroke cycle (transition of the propulsion phases between sides). Post-hoc comparison revealed a significant difference between group #1 and group #3 only in SPM analysis. Researchers, coaches, and practitioners should know that both measurement approaches can be used simultaneously. However, SPM offers more sensitive and accurate results about the swimmers' stroke cycle.